Abu Jahl and his relationship with the Prophet (The International Journal of Educational Sciences and Arts, 2026)
This study addresses Abu Jahl, Amr ibn Hisham al-Makhzumi, one of the foremost leaders of Quraysh, who opposed Islam from its very emergence despite his certainty regarding the truthfulness of its Prophet, Peace and Blessings of Allah be upon him. Notwithstanding the kinship that bound him to the Messenger of Islam, Peace and Blessings of Allah be upon him, he showed relentless hostility toward Islam from its inception, driven by arrogance and envy. His opposition manifested in mocking the Qur'an, inflicting verbal and physical harm upon the Messenger of Allah, Peace and Blessings of Allah be upon him, persecuting the weak among the Muslims, confronting every noble of Quraysh whose heart inclined toward Islam, and devising conspiracies against Islam and its Prophet. He also attempted to prevent the Prophet, Peace and Blessings of Allah be upon him, from migration by plotting to assassinate him. Furthermore, he mobilized the army of Quraysh and its leading figures to march toward Badr, leading to the Great Battle of Badr, where this army suffered defeat despite its numerical strength and preparation.The confrontation concluded with the killing of the prominent leaders of Quraysh, and his end was humiliating, as he was slain in this battle at the age of seventy.
Keywords: The prophet; Abu Jahl; Mecca; Quraysh; Battle of Badr